(untitled) (Scientific journal of the Fergana State University, 2023)
This article examines the conceptual features of military-practical physical training and its significant aspects in young people. At the same time, the task of the conceptual features of military-practical physical training in the framework of Pedagogical Sciences, the methodology of training personnel were analyzed.